2018
DOI: 10.1111/ppc.12314
|View full text |Cite
|
Sign up to set email alerts
|

Prejudice against obesity in university students studying in health‐related departments

Abstract: According to the results of the study, university students who will be future nurses and other healthcare professionals, tend toward obesity prejudice, negatively impacting health care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 17 publications
5
18
1
Order By: Relevance
“…No statistically significant difference was found between health personnel's' obesity prejudice scale average score and age, gender, marital status, income, level of education, profession, BMI and years in profession ( Table 1, Tablo 2). Similarly, no association was found between age and obesity prejudice scale average scores in studies conducted (10,12). Contrary to our study, in a study conducted on primary healthcare professionals, those with more years of employment in the profession were found to be more biased towards obese people (18).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…No statistically significant difference was found between health personnel's' obesity prejudice scale average score and age, gender, marital status, income, level of education, profession, BMI and years in profession ( Table 1, Tablo 2). Similarly, no association was found between age and obesity prejudice scale average scores in studies conducted (10,12). Contrary to our study, in a study conducted on primary healthcare professionals, those with more years of employment in the profession were found to be more biased towards obese people (18).…”
Section: Discussioncontrasting
confidence: 99%
“…That is, the health personnel who did not consider themselves as prejudiced against obese individuals were in fact more prejudiced than others. Similarly, in another study, it was found that the individuals who stated that they were unprejudiced against obese individuals were found to have higher obesity prejudice average scores than the individuals who stated that they were prejudiced (12). The reason why individuals had higher average scores although they stated that they were unprejudiced brings to mind that health personnel can have implicit (latent) prejudice that they are not aware of.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…For example, in countries with relatively little racial variability, other forms of implicit bias such as weight (eg, eastern Asian countries), immigrants (eg, western European countries), or religion (eg, Middle Eastern countries) might play an important role in patient care. [13][14][15] In this Viewpoint, we highlight three crucial translational gaps in implicit bias training that are used in medical schools and other health organisations. We suggest that before medical schools and other health organisations invest further time and financial resources in implicit bias training, they should pause, take a step back, and critically evaluate the grounding and effectiveness of current training.…”
mentioning
confidence: 99%